On Subjectivist Interpretation of Probability - Nekrašas, Evaldas (Problemos, 1973)
According to the subjectivist interpretation of probability, the latter is understood as an individual degree of belief in some hypothesis or event. Though being very old, this conception is often disputed. In some fields of science, however, such as the theory of solutions, psychology and related sciences, the above interpretation is found to make sense if, while operating with probabilities, definite restrictions are observed: Firstly, it is inadmissible to confuse the degrees of belief of different individuals and, secondly, it is substantial that the degrees of belief were coherent, i.e., would conform to the axioms of the theory or probabilities. An attempt to solve the problem by finding expedient and rational solutions, on the other hand, makes it necessary to estimate the factual success that presumes a reference to the statements formulated in the terms of empirical probability